2006
DOI: 10.1124/mol.106.023002
|View full text |Cite
|
Sign up to set email alerts
|

Mutations Distal to the Substrate Site Can Affect Varicella Zoster Virus Thymidine Kinase Activity: Implications for Drug Design

Abstract: Varicella zoster virus encodes a thymidine kinase responsible for the activation of antiherpetic nucleoside prodrugs such as acyclovir. In addition, herpes virus thymidine kinases are being explored in gene/chemotherapy strategies aimed at developing novel antitumor therapies. To investigate and improve compound selectivity, we report here structure-based site-directed mutagenesis studies of varicella zoster virus thymidine kinase (VZVTK). Earlier reports showed that mutating residues at the core of the VZVTK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The kinetic analysis of 145_V153A, showed a higher turnover number compared to the WT (126 min −1 , Table II) but a decreased affinity. Previous work involving SDM of enzymes have shown that distal mutations can have an effect on activity and substrate affinity of the enzyme (Ardissone et al, 2005; El et al, 2006; Lee and Goodey, 2011). Lee and Goodey have described possible reasons for these indirect effects based on inter molecular relationships, charge distribution and conformational motion of proteins (Lee and Goodey, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The kinetic analysis of 145_V153A, showed a higher turnover number compared to the WT (126 min −1 , Table II) but a decreased affinity. Previous work involving SDM of enzymes have shown that distal mutations can have an effect on activity and substrate affinity of the enzyme (Ardissone et al, 2005; El et al, 2006; Lee and Goodey, 2011). Lee and Goodey have described possible reasons for these indirect effects based on inter molecular relationships, charge distribution and conformational motion of proteins (Lee and Goodey, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For engineering enzyme specificity, it has been shown that a rational mutagenesis approach—primarily focused on residues lining a substrate binding pocket—provides greater payoffs than random mutagenesis (that is, error-prone PCR)11213. However, it is no secret that distant (>10 Å) mutations can have significant effects on catalytic function1314151617181920. For example, in a classic paper Oue et al 20.…”
mentioning
confidence: 99%
“…Thus, the molecular basis for resistance to ACV is linked to mutations in either the viral TK or the DNA Pol gene. Herpesvirus TKs are able to transfer a ␥-phosphoryl group from ATP to the 5= hydroxyl group of thymidine (13). In addition, VZV and HSV-1 TKs possess thymidylate kinase activity, which converts dTMP to dTDP.…”
mentioning
confidence: 99%